AKTIVITAS ANTIHIPERURESEMIA KOMBINASI EKSTRAK RIMPANG LENGKUAS (Alpinia galanga L.) DAN ALLOPURINOL PADA MENCIT PUTIH JANTAN GALUR SWISS - Devi Ika Kurnianingtyas Solikhati; Endang Istriningsih (Parapemikir : Jurnal Ilmiah Farmasi, 2020)
Hyperuresemia is an elevated level of uric acid in the blood above normal. Allopurinol is a drug that is often used to treat hyperuresemia, but at high levels it can cause various side effects, one of which is hepatotoxic. Giving galangal rhizome extract combination which has been proven as a hepatoprotector and antihyperuresemia, is expected to reduce the side effects of allopurinol and provide a synergistic effect in reducing uric acid levels in the blood. This study used Group I which gave a negative suspension which was given a 0.5% Na CMC suspension; Kempok II was given allopurinol 10 mg / kg BW; Group III was given galangal rhizome extract at a dose of 9.1 mg / 20 g BW and group IV was given a combination of galangal rhizome extract dose of 4.55 mg / 20 g BW and allopurinol 5 mg / kg BW. The results of measurement of uric acid levels in the blood showed decreased levels of uric acid in the blood of the negative control group, allopurinol, galangal, and a combined combination - contributing were 6.48 mg / dl; 30mg / dl; 30.96 mg / dl; and 59.52mg / dl. The post hoc test results showed a decrease in the levels of uric acid in the combined blood and the single group showed a difference, this showed a synergistic effect of the administration of a combination of allopurinol and galangal extract. This synergistic effect is related to the content of galangal extract which can inhibit allopurinolKeyword – Antihyperuresemia, Gout, Alpinia Galanga L., Allopurinol